Organic Phosphorus in the Environment 2004
DOI: 10.1079/9780851998220.0021
|View full text |Cite
|
Sign up to set email alerts
|

Using phosphorus-31 nuclear magnetic resonance spectroscopy to characterize organic phosphorus in environmental samples.

Abstract: This paper reviews the use of 31P nuclear magnetic resonance (NMR) spectroscopy for soil, water and other environmental samples (i.e., forest floor material, alkaline agricultural soil, marine sediment, sewage sludge and humic acid). After a brief overview of the principles of NMR spectroscopy, the requirements for a successful NMR experiment are described. A literature on 31P NMR spectroscopy in soils and environmental samples is also reviewed, followed by suggestions for future research needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 0 publications
1
75
0
Order By: Relevance
“…Even when using a pulse angle of 90° and a very high relaxation time (15 s) (Cade-Menun, 2005;McDowell et al, 2006), no P was detected in the polyphosphate and phosphonate categories in our soil samples. Similar results were obtained by Rheinheimer et al (2002) and Gatiboni et al (2005), with soils from the same Brazilian region.…”
Section: P-nmr Spectramentioning
confidence: 65%
See 1 more Smart Citation
“…Even when using a pulse angle of 90° and a very high relaxation time (15 s) (Cade-Menun, 2005;McDowell et al, 2006), no P was detected in the polyphosphate and phosphonate categories in our soil samples. Similar results were obtained by Rheinheimer et al (2002) and Gatiboni et al (2005), with soils from the same Brazilian region.…”
Section: P-nmr Spectramentioning
confidence: 65%
“…An amount of 0.3 mL D 2 O was added and the mixture vortex-stirred for 5 min. After standing for 120 min, the supernatant was separated by centrifugation (2,500 rpm for 15 min), filtered through a 0.22 µm membrane and transferred to 5 mm NMR tubes (Cade-Menun, 2005). The 31 P spectra were obtained in a Bruker Advance DPX 400 spectrometer at a frequency of 162 MHz with proton decoupling.…”
Section: P-nmr Analysismentioning
confidence: 99%
“…Phosphorus in solution is normally considered to be orthophosphate (Soluble Reactive Phosphate or SRP) and is taken by different component members of an aquatic ecosystem. Boyd and Musig (1981) demonstrated that planktons in fish ponds absorbed an average of 41% of 0.30 mg/L addition of orthophosphate within 24 hours; however phosphorus that is not absorbed by planktons is rapidly absorbed mud (Hupfer, et al, 2004;Cade-menum, 2005). Pelagic invertebrates not only transform, they can also translocate the recycled phosphorus within the system (Shapiro, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…[10] At the other end of the spectrum researchers have used several sophisticated (and expensive) instruments to explore organic P speciation including ultra-high field mass spectrometry, [11] X-ray absorption near edge structure (XANES) spectroscopy [12,13] (which requires a source of synchrotron radiation), and solution and solid state 31 P NMR spectroscopy. [14] Of these more sophisticated approaches, based on the number of publications, solution 31 P NMR spectroscopy appears to have been the most influential.…”
Section: -X)-mentioning
confidence: 99%